Proposal for an Alliance Between Healthcare and Legal Area Professionals for Shared Public Health and Preventive Strategies in Italy and Europe - Costantino, Claudio; Mazzucco, Walter; Restivo, Vincenzo; Mura, Ida Iolanda; Fara, Gaetano Maria; Giammanco, Giuseppe; Vecchio Verderame, Sabrina; Messano, Giuseppe Alessio; Maida, Carmelo Massimo; Casuccio, Alessandra; Vitale, Francesco (Frontiers in Public Health, 2020)
Following the implementation of the new Italian legislation on responsibility of healthcare workers, a multi-professional framework, involving representatives of the Italian public health professionals and legal professionals expert in the field, drafted a proposal of the actionable recommendations to be implemented in the management of civil and penal disputes arising from the practice of public health interventions. The interactive framework experienced that in order to prevent legal disputes concerning public health 1. the "best scientific evidence available" should be taken into account to update guidelines in support of decision-making in the health sector; 2. multidisciplinary alliance between public health and legal area professionals should be encouraged in the resolution of legal disputes concerning public health and should be promoted both at national and European level.